CLINICOPATHOLOGIC PECULIARITIES OF NONSPECIFIC ULCERATIVE COLITIS AND CROHN'S DISEASE - S. D. Strelkova; G. Z. Murzina; D. A. Valetdinov; S. N. Styajkina; N. A. Kiryanov; G. I. Tihomirova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Currently, inflammatory bowel diseases (IBD), in nonspecific ulcerative colitis (NUC) and Crohn's disease (CD), are an extremely urgent problem. The incidence of both ulcerative colitis and Crohn's disease worldwide is increasing every year, and mainly among the working-age population, which makes inflammatory bowel disease (IBD) a socially significant disease. The clinical picture of IBD is diverse, which often makes it difficult to timely diagnose and prescribe adequate therapy and inevitably negatively affects the prognosis of diseases. Here are some of the characteristics of the NUC and CD. The histogram results of numerous studies indicate the following: in Crohn's disease (CD), the thickness of the intestinal wall is often significantly increased. In the mucous membrane, slit-like ulcerative defects are detected, in the bottom of which there are signs of inflammation in the form of infiltration of the bottom of the ulcers by leukocytes, lymphocytes, histiocytes. As for colitis, based on these clinical cases, it can be concluded that children and adolescents are  characterized by a total lesion of the colon and the appearance of segmental forms. In adult patients, distal colitis, the so-called proctosigmoiditis, prevails.  On examination, the mucous membrane was edematous, vividly hyperemic,  edematous, with superficial erosions.